2023
DOI: 10.1021/acscatal.3c02209
|View full text |Cite
|
Sign up to set email alerts
|

Intermolecular Metal-Catalyzed C–C Coupling of Unactivated Alcohols or Aldehydes for Convergent Ketone Construction beyond Premetalated Reagents

Abstract: Intermolecular metal-catalyzed C−C couplings of unactivated primary alcohols or aldehydes to form ketones are catalogued. Reactions are classified on the basis of pronucleophile. Protocols involving premetalated reagents or reactants that incorporate directing groups are not covered. These methods represent an emerging alternative to classical multistep protocols for ketone construction that exploit premetalated reagents and/or steps devoted to redox manipulations and carboxylic acid derivatization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 119 publications
0
2
0
Order By: Relevance
“…Ketone is an essential molecular scaffold commonly found in natural products, pharmaceuticals, and agrochemicals . Among various synthetic strategies, the cross-coupling reactions play an important role in ketone synthesis . As an important class of coupling reagents, organoboron compounds are versatile building blocks highly prized in modern organic chemistry, probably due to their wide availability and structural diversity .…”
Section: Introductionmentioning
confidence: 99%
“…Ketone is an essential molecular scaffold commonly found in natural products, pharmaceuticals, and agrochemicals . Among various synthetic strategies, the cross-coupling reactions play an important role in ketone synthesis . As an important class of coupling reagents, organoboron compounds are versatile building blocks highly prized in modern organic chemistry, probably due to their wide availability and structural diversity .…”
Section: Introductionmentioning
confidence: 99%
“…Besides, noteworthy developments have been reported under transition metal catalysis for the synthesis of α-branched ketones from simple ketones via the borrowing hydrogen (BH)/hydrogen atom-transfer (HA) strategy using alcohols as alkylating agents . In recent years, alcohol has been employed as an alkylating source for various C–C and C–N bond-forming reactions through the borrowing hydrogen (BH) and acceptorless dehydrogenative coupling (ADC) strategies (Figure a–c). The BH approach is one of the most powerful methodologies utilizing readily available alcohols as an alkylating source and producing green byproducts such as water, thereby avoiding the formation of toxic byproducts.…”
Section: Introductionmentioning
confidence: 99%
“…Alcohols belong to wide available compounds in the chemistry industry; the development of versatile methodologies for assembling structural complex molecules starting from alcohols is of great interest . Although the cross-coupling reactions between alcohols and aldehydes provide a direct approach to construct new C–C σ bonds and CC double bonds, the range of alcohols is generally limited to primary alcohols and secondary alcohols . For example, Han et al reported an organophosphate-mediated C–C coupling of primary alcohols with aldehydes via the Michaelis–Arbuzov reaction, in which primary alcohols could be easily converted to alkyl phosphonates, followed by nucleophilic attack on aldehydes to furnish alkenes (Scheme , eq a) .…”
Section: Introductionmentioning
confidence: 99%